Cost-benefit analysis of small hydroelectric generation project utilizing resident volunteers - Eiji Ohno; Ryuta Mori; Akira Matsumoto (European Regional Science Association (ERSA), 2016)
Small-scale renewable electricity generation projects have the potential to address not just the need to reduce greenhouse gas emissions to combat climate change, but also to provide local, sustainable economic and community revitalization. In this paper, we have proposed a small hydroelectric generation project with citizen participation which includes cooperation in some activities such as cleaning and patrols, and have evaluated the project economically by using the regional input-output (I-O) analysis in which the willingness to work (WTW) is incorporated. The WTW for the project have been estimated by using the conjoint analysis as a function of its various attributes, namely revenue from the project's electricity sales, profits earned for the local community, and rewards given to contributors. The results show that the amount of WTW provided by resident volunteers will increase with increasing unit value of reward, but the amount of reward paid to volunteers will also increase. On the other hand, the operating income of the establishment that has contracted maintenance of the small hydroelectric supply sector will decrease, and its influence will spread through the inter-industry relations. Then, we have analyzed such economic ripple effect by using the regional I-O table for analysis of small hydroelectric generation project. By considering the range of the "unit value of reward" and the "substitution rate of resident volunteers", even if the project is deficit, we have found a good countermeasure which can be expected positive effects. As a result, it is possible to reduce the subsidies of regional governments with respect to the project, and it is possible to devote that amount of budget to improvement of other administrative services. Although introduction of volunteer activities is finished when the amount of WTW exceeds the consignment work load in this case study, more volunteer activities may be introduced if external economic benefits of volunteers are expected. For example, if the bond of community are strengthened by that residents participate in volunteer activities, the bond strengthened can compensate for the lack of government services such as disaster prevention and welfare, and improvement of resident satisfaction may be expected. By evaluating such external economic benefits and practicing social cost benefit analysis, it is possible to discuss that more volunteer activities should be introduced or not. Such external economic benefits can be measured by the opportunity cost of volunteer activities or the time value of WTW, but this matter will be discussed at the next stage. When this type of small hydroelectric generation project utilizing resident volunteers is introduced, household utility levels increase. Understanding the dynamism between these factors can allow regional governments to adapt the scheme to best fit the needs of individual regions.
Keywords: Q42; Q51; R13; 330; small hydroelectric generation; resident volunteers; regional input-output analysis; willingness to work